2013
DOI: 10.1186/1471-2458-13-794
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity counseling in primary health care in Brazil: a national study on prevalence and associated factors

Abstract: BackgroundThe aim of this study was to determine the prevalence and correlates of physical activity counseling among physicians and nurses working in primary health care in Brazil.MethodsA phone survey was carried out in 2011 with professionals working in primary health care in Brazil. The target sample consisted of 1,600 randomly selected primary care units covering all regions of the country. We successfully interviewed 529 professionals within the sampled units; 182 physicians and 347 nurses. The overall re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
1
38

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(125 citation statements)
references
References 35 publications
1
85
1
38
Order By: Relevance
“…ese professionals have been pointed out as being extremely relevant for health promotion in the SUS. A survey done with a sample of professionals working in primary health units in Brazil in 2011 showed that doctors and nurses considered physical education professionals as the main professionals responsible for promoting physical activity within the teams 24 . A recent systematic review study emphasized the increase in the participation of physical education professionals in the actions carried out in the scope of primary health care in Brazil 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ese professionals have been pointed out as being extremely relevant for health promotion in the SUS. A survey done with a sample of professionals working in primary health units in Brazil in 2011 showed that doctors and nurses considered physical education professionals as the main professionals responsible for promoting physical activity within the teams 24 . A recent systematic review study emphasized the increase in the participation of physical education professionals in the actions carried out in the scope of primary health care in Brazil 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the interventions to promote physical activity performed in primary health units in Brazil are already coordinated by physical education professionals 32 . Health managers and professionals working in primary health care also recognize physical education professionals as very important in actions to promote physical activity in SUS 24,34 . Regarding healthy eating, it was observed that food and nutritional surveillance was advanced in the SUS 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Only 25% of the cities had plan for training health professionals for develop the actions in "Academia da Saúde". Studies conducted with health professionals in Brazil showed that knowledge is important for physical activity and healthy food promotion in primary health care units 26,27 . The food guide for Brazilian population and book about physical activity promotion in primary health care settings can be good instruments for training these professionals 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Florindo et al 10 showed that nutritionists and physical education professionals are very important for promotion healthy food and physical activity in these cities with "Academia da Saúde" 10 . And survey conducted in primary health care settings in Brazil showed that physicians and nurses are important for physical activity promotion 26 . However, is necessary improve actions for training these professionals.…”
Section: Discussionmentioning
confidence: 99%
“…O Ministério da Saúde, por meio do Sistema Único de Saúde (SUS), tem investido em ações de promoção da atividade física 19 e o cenário atual é promissor na opinião de médicos e enfermeiros que atuam na Atenção Básica que consideram importante promover atividade física nas UBS 20 . No entanto, os ACS ainda são pouco envolvidos como atores importantes na promoção da atividade física no Brasil, apesar de seu potencial por possuírem características de atuação singulares e manterem contato frequente com as pessoas da comunidade, dada que a maior parte das suas ações é realizada extraunidade.…”
Section: Introductionunclassified